Víctimas y victimarias: el ejercicio de la violencia en Pelea de gallos de María Fernanda Ampuero - Jaramillo Cumbicus, Erika Mayte (2024)
The present work focuses on analyzing the dynamics and roles of violence in the female characters that appear in the short story book "Pelea de gallos" by María Fernanda Ampuero. To achieve the objectives, the following questions are addressed: How does violence manifest towards women in the stories of "Pelea de gallos" by Ampuero? What are the conditions under which the exercise of violence arises? Is there a transformation from victim to perpetrator in female characters? In the theoretical framework, gender violence in socio-cultural spaces and literature postulates are presented. The methodology used applies a qualitative approach, given the interpretative nature of the feminist literary criticism. A literary analysis matrix is developed to extract data based on the three specific objectives. Thus, it is found that in "Pelea de gallos," women are both victims and perpetrators. The victimization of women occurs within the spheres of a patriarchal society characterized by conditions of social inequality, which legitimizes gender violence. The accumulation of risk factors such as race, gender, and economic status multiplies the possibility of violence occurring in these individuals. The woman as a perpetrator symbolically overturns the image of an idealized woman and breaks stereotypes surrounding roles of violence. In the transition from victim to perpetrator, an evident emotional transformation of the female characters is observed; from presenting low self-esteem and submission, the female perpetrator is depicted as a brutal and bloodthirsty woman. Finally, the transformation from victim to perpetrator demystifies the passivity and socially imposed roles of women, portraying them as individuals with human qualities.